-
Notifications
You must be signed in to change notification settings - Fork 4
/
Copy pathCox_Galois_Chapter3.tex
484 lines (360 loc) · 21.2 KB
/
Cox_Galois_Chapter3.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
347
348
349
350
351
352
353
354
355
356
357
358
359
360
361
362
363
364
365
366
367
368
369
370
371
372
373
374
375
376
377
378
379
380
381
382
383
384
385
386
387
388
389
390
391
392
393
394
395
396
397
398
399
400
401
402
403
404
405
406
407
408
409
410
411
412
413
414
415
416
417
418
419
420
421
422
423
424
425
426
427
428
429
430
431
432
433
434
435
436
437
438
439
440
441
442
443
444
445
446
447
448
449
450
451
452
453
454
455
456
457
458
459
460
461
462
463
464
465
466
467
468
469
470
471
472
473
474
475
476
477
478
479
480
481
482
483
484
%&LaTeX
\documentclass[11pt,a4paper]{article}
\usepackage[frenchb,english]{babel}
\usepackage[applemac]{inputenc}
\usepackage[OT1]{fontenc}
\usepackage[]{graphicx}
\usepackage{amsmath}
\usepackage{amsfonts}
\usepackage{amsthm}
\usepackage{amssymb}
%\input{8bitdefs}
% marges
\topmargin 10pt
\headsep 10pt
\headheight 10pt
\marginparwidth 30pt
\oddsidemargin 40pt
\evensidemargin 40pt
\footskip 30pt
\textheight 670pt
\textwidth 420pt
\def\imp{\Rightarrow}
\def\gcro{\mbox{[\hspace{-.15em}[}}% intervalles d'entiers
\def\dcro{\mbox{]\hspace{-.15em}]}}
\newcommand{\be} {\begin{enumerate}}
\newcommand{\ee} {\end{enumerate}}
\newcommand{\deb}{\begin{eqnarray*}}
\newcommand{\fin}{\end{eqnarray*}}
\newcommand{\ssi} {si et seulement si }
\newcommand{\D}{\mathrm{d}}
\newcommand{\Q}{\mathbb{Q}}
\newcommand{\Z}{\mathbb{Z}}
\newcommand{\N}{\mathbb{N}}
\newcommand{\R}{\mathbb{R}}
\newcommand{\C}{\mathbb{C}}
\newcommand{\F}{\mathbb{F}}
\newcommand{\re}{\,\mathrm{Re}\,}
\newcommand{\ord}{\mathrm{ord}}
\newcommand{\legendre}[2]{\genfrac{(}{)}{}{}{#1}{#2}}
\title{Solutions to David A.Cox "Galois Theory''}
\author{Richard Ganaye}
\refstepcounter{section} \refstepcounter{section}
\begin{document}
\section{Chapter 3}
\subsection{THE EXISTENCE OF ROOTS}
\paragraph{Ex. 3.1.1}
{\it This exercise is concerned with the proof of Proposition 3.1.1. Suppose that $f,g,h \in F[x]$ are polynomials such that $f$ is nonzero and $f=gh$. Also let $I = \langle g \rangle$.
\begin{enumerate}
\item[(a)] Prove that $g$ constant if and only if $I = F[x]$.
\item[(b)] Prove that $h$ constant if and only if $I = \langle f \rangle$.
\end{enumerate}
}
\begin{proof}
Let $f,g,h \in F[x], f\neq 0, f=gh, I = \langle g \rangle$.
\begin{enumerate}
\item[(a)]
$\bullet$ Suppose that $g = \lambda \in F$ is a constant. As $f \neq 0$ and $f = gh$, then $g\ne 0$, so $\lambda \neq 0$.
Let $p \in F[x]$ any polynomial. Then $p = \lambda (\frac{1}{\lambda} p ) = (\frac{1}{\lambda} p ) g \in \langle g \rangle$, thus $F[x] \subset \langle g \rangle$. Moreover $\langle g \rangle \subset F[x]$, so $$F[x] = \langle g \rangle = I.$$
$\bullet$ Conversely, if $F[x] = I = \langle g \rangle$, then $ 1 \in \langle g \rangle$, so $1 = g u, u \in F[x]$, hence $0 = \deg(g)+\deg(u)$, therefore $\deg(g) = 0$, so $g \in F$ is a nonzero constant.
$$g \in F^* \iff \langle g \rangle = F[x].$$
\item[(b)] $\bullet$ If $h = \mu \in F$ is a constant, then $\mu\neq 0$ (since $f\ne 0$), and $f =\mu g, \mu \in F^*$.
If $p \in \langle f \rangle$, then $p = u f, u \in F[x]$, thus $p = \mu u g \in \langle g \rangle$, so $\langle f \rangle \subset \langle g \rangle$.
If $p \in \langle g \rangle$, then $p = q g, q \in F[x]$, thus $p = \mu^{-1} q f \in \langle f \rangle$, so $\langle g \rangle \subset \langle f \rangle$.
$$\langle f \rangle = \langle g \rangle = I.$$
$\bullet$ Conversely, if $\langle f \rangle = \langle g \rangle,$ then $g \in \langle f \rangle$ , $g = v f, v \in F[x]$, thus $g = v gh$. As $f = gh\neq 0, g \neq 0$, thus $1 = vh$, therefore $h \in F^*$ is a constant.
$$h \in F^* \iff I =\langle f \rangle.$$
\end{enumerate}
\end{proof}
\paragraph{Ex. 3.1.2}
{\it Let $F$ and $L$ be fields, and let $\varphi : F \to L$ be a ring homomorphism. Prove that $\varphi$ is one-to-one and that we get an isomorphism $\varphi : F \simeq \varphi(F)$.
}
\begin{proof}
Let $x \in F$. If $x\ne 0$, then $x\cdot x^{-1} = 1$, thus $\varphi(x) \varphi(x^{-1}) = 1$, so $\varphi(x) \ne 0$.
For all $x\in F$, $x \ne 0 \Rightarrow \varphi(x) \ne 0$, therefore $\varphi(x) = 0 \Rightarrow x =0$, so $\ker(\varphi) = \{0\}$ and $\varphi$ is injective.
Consequently, the corestriction $F \to \varphi(F), x \mapsto \varphi(x)$ is a bijection, so it is a ring isomorphism $\varphi : F \simeq \varphi(F)$.
\end{proof}
\paragraph{Ex. 3.1.3}
{\it Let $I \subset F[x]$ be an ideal, and define $\varphi : F \to F[x]/I$ by $\varphi(a) = a + I$. Prove carefully that $\varphi$ is a ring homomorphism.
}
\begin{proof}
Let $a,b \in A = F[x]$. Suppose that $a+I = a'+I$ and $b+I = b'+I$.
Then $a' =a + u, u \in I, b' = b+v, v\in I$, so $a'+b' = a+b + u+v$, where $u+v \in I$, thus $a+b+I = a'+b'+I$.
$a'b' = ab+ bu+av + uv$, where $bu+av + uv \in I$, so $ab+ I = a'b'+I$.
The equivalence relation $\sim$ defined on $A$ as $a \sim a' \iff a+ I = a'+ I (\iff a' - a \in I)$ is so compatible with addition and multiplication in $A$, and the class of an element $a \in A$ is $a+I$. We can so define sum and product of two classes by
\begin{align}
(a+I) +(b+I) &= a+b+I, \label{eq3.1.3:1}\\
(a+I) (b+I) &= ab+I.\label{eq3.1.3:2}
\end{align}
If $\varphi : A \to A/I$ is defined by $\varphi(a) = a+I$, then \eqref{eq3.1.3:1} and \eqref{eq3.1.3:2} are written
$$\varphi(a)+ \varphi(b) = \varphi(a+b) , \varphi(a) \varphi(b) = \varphi(ab)$$
Moreover $\varphi(1) = 1+I$ is the multiplicative identity of $A/I$.
$\varphi : A \to A/I$ is a ring homomorphism.
\end{proof}
\paragraph{Ex. 3.1.4}
{\it In your abstract algebra text, review the definition of the field of fractions of an integral domain and verify that (3.3) is the correct definition of $a/b$ for $a,b \in \Z, b\ne 0$.
}
\begin{proof}
The relation $\sim$ on $\mathbb{Z} \times \mathbb{Z}^*$ defined by
$$(a,b) \sim (c,d) \iff ad = bc$$
is an equivalence relation.
The class of $(a,b)$, written $\frac{a}{b}$ is so the set
$$\frac{a}{b} = \{(c,d)\in \mathbb{Z} \times \mathbb{Z}^* \ \vert \ ad = bc \}.$$
\end{proof}
\paragraph{Ex. 3.1.5}
{\it Let $f \in F[x]$ be irreducible, and let $g+\langle f \rangle$ be a nonzero coset in the quotient ring $L = F[x]/\langle f \rangle$.
\begin{enumerate}
\item[(a)] Show that $f$ and $g$ are relatively prime and conclude that $Af+Bg=1$, where $A,B$ are polynomials in $F[x]$.
\item[(b)] Show that $B + \langle f \rangle$ is the multiplicative inverse of $g + \langle f \rangle $ in $L$.
\end{enumerate}
}
\begin{proof}
Let $f \in F[x]$ be irreducible, and let $L =F[x]/\langle f \rangle$ the quotient ring.
\begin{enumerate}
\item[(a)] Let $\overline{g} \in L, \overline{g} \neq \overline{0}$, that is to say $g + \langle f \rangle \neq 0 + \langle f \rangle$, which is equivalent to $ g \not \in \langle f \rangle$, or $f \nmid g$ (in $F[x]$).
Let $u$ a common divisor of $f$ and $g$. Since $f$ is irreducible, either $u$ is a nonzero constant, or $f = k u, k \in F^*$, i.e., $u$ is associate to $f$. But in this last case, $u = k^{-1} f$ and $f$ divides $u$, which divides $g$, so $f \mid g$, in contradiction with the hypothesis.
So the only common divisors of $f,g$ are the nonzero constants, thus $f \wedge g = 1$.
By B\'ezout theorem, there exist polynomials $A,B \in k[x]$ such that
$$1 = A f + B g.$$
\item[(b)]
As $\overline{f} = f + \langle f \rangle = \overline{0}$, $\overline{1} = \overline{A}\, \overline{f} + \overline{B} \overline{g} = \overline{B} \overline{g}$, which we can write
$$1 + \langle f \rangle = (B + \langle f \rangle )(g+ \langle f \rangle).$$
So $B+\langle f \rangle$ is the inverse of $g+ \langle f \rangle$ in $L =F[x]/\langle f \rangle$.
\end{enumerate}
\end{proof}
\paragraph{Ex. 3.1.6}
{\it Apply the method of Exercise 5 to find the multiplicative inverse of the coset $1+x+\langle x^2+x+1\rangle$ in the field $\Q[x]/\langle x^2+x+1 \rangle$.
}
\begin{proof}
$f = x^2+x+1$ has no root in $\mathbb{Q}$ is has degree 2, therefore $f$ is irreducible on $\mathbb{Q}$, and consequently $\Q[x]/\langle f \rangle$ is a field.
Moreover $-x(x+1) + (x^2+x+1) = 1$ is a B\'ezout's relation between $x+1$ and $x^2+x+1$. This gives the following equality in $\Q[x]/\langle f \rangle$:
$$(-x + \langle f \rangle) (x+1+\langle f \rangle) + (x^2+x+1) + \langle f \rangle = 1 + \langle f \rangle,$$
so
$$(-x + \langle f \rangle) (x+1+\langle f \rangle) = 1 + \langle f \rangle.$$
$-x + \langle f \rangle$ is the inverse of $x+1+\langle f \rangle$ in $\Q[x]/\langle f \rangle$.
\end{proof}
\subsection{THE FUNDAMENTAL THEOREM OF ALGEBRA}
\paragraph{Ex. 3.2.1}
{\it For $f \in \C[x]$, define $\overline{f}$ as in (3.5).
\begin{enumerate}
\item[(a)] Show carefully that $\overline{fg} = \overline{f}\, \overline{g}$ for $f,g \in \C[x]$.
\item[(b)] Let $\alpha \in \C$. Show that $\overline{f}(\alpha) = 0$ implies that $f(\overline{\alpha} )= 0$.
\end{enumerate}
}
\begin{proof}
\begin{enumerate}
\item[(a)]
Let $f = \sum\limits_{i=0}^n{a_ix^i}, g = \sum\limits_{j=0}^m{b_jx^i} \in \mathbb{C}[x]$.
By definition of the product of polynomials,
$$fg = \sum_{k=0}^{n+m}c_kx^{k}, \ \mathrm{with} \ c_k =\sum_{i+j = k}a_ib_j = \sum_{i=0}^k a_i b_{k-i}$$
Then, using the fact that conjugation is a field automorphism in $\mathbb{C}$,
\begin{align*}
\overline{fg} &= \sum_{k=0}^{n+m}\overline{c_k}x^{k}\\
&=\sum_{k=0}^{n+m}\overline{\sum_{i+j = k}a_ib_j} x^k\\
&=\sum_{k=0}^{n+m}\sum_{i+j = k}\overline{a_i} \overline{b_j} x^k\\
&=\sum\limits_{i=0}^n{\overline{a_i}x^i} \sum\limits_{j=0}^n\overline{b_j}x^j\\
&=\overline{f} \overline{g}.
\end{align*}
\item[(b)] If $f \in \C[x]$ and $\alpha \in \C$,
\begin{align*}
\overline{f}(\alpha) = 0 &\Rightarrow \sum\limits_{i=0}^n\overline{a_i}\alpha^i= 0\\
&\Rightarrow \overline{\sum\limits_{i=0}^n\overline{a_i}\alpha^i} = \overline{0}=0\\
&\Rightarrow \sum\limits_{i=0}^n a_i \overline{\alpha}^i=0\\
&\Rightarrow f(\overline{\alpha}) = 0.
\end{align*}
\end{enumerate}
\end{proof}
\paragraph{Ex. 3.2.2}
{\it In Section A.2, we use polar coordinates to construct square (and higher) roots of complex numbers. In this exercise, you will give an elementary argument that every complex number has a square root. The only fact you will use (besides standard algebra) is that every positive real number has a real square root.
\begin{enumerate}
\item[(a)] First explain why every real number has a square root in $\C$.
\item[(b)] Now fix $a+bi \in \C$ with $b \ne 0$. For $x,y \in \R$, show that the equation $(x+iy)^2 = a+bi$ is equivalent to the equations
$$x^2-y^2 = a, \qquad 2xy = b.$$
\item[(c)] Show that the equation of part (b) are equivalent to
$$x^2 =\frac{a\pm \sqrt{a^2+b^2}}{2}, \qquad y = \frac{b}{2x}.$$
Also show that $x\ne 0$ and that $a\pm \sqrt{a^2+b^2}$ is positive when we choose the $+$ sign in the formula for $x^2$.
\item[(d)] Conclude that $a+bi$ has a square root in $\C$.
\end{enumerate}
}
\begin{proof}
\begin{enumerate}
\item[(a)]
We know that the equation $x^2 = a$ has a real solution if $a\geq 0$ (see Ex. 3.2.3).
Therefore, if $a \in \mathbb{R}^-_*$, there exists $b\in \mathbb{R}^+$ such that $b^2 = -a = \vert a \vert$.
Thus $(ib)^2 = a$.
Conclusion: Every $a \in \mathbb{R}$ has a square root in $\mathbb{C}$.
\item[(b,c,d)] Let $z = a+ib,\ a,b \in \mathbb{R}$, and $Z = x+iy,\ x,y \in \mathbb{R}$ two complex numbers.
\begin{align*}
z^2 = Z &\iff (a+ ib)^2 = x+iy\\
&\iff (a+ ib)^2 = x+iy \ \mathrm{and} \ \vert a+ ib\vert ^2 = \vert x+iy\vert \\
&\iff a^2 - b^2 +2abi = x+iy\ \mathrm{and} \ a^2+b^2 = \sqrt{x^2+y^2}\\
&\iff a^2 - b^2 = x, a^2 + b^2 =\sqrt{x^2+y^2}, 2ab = y.
\end{align*}
The system of equations
$
\left\{
\begin{array}{ccc}
a^2 - b^2 &=& x, \\
a^2 + b^2 &=&\sqrt{x^2+y^2},
\end{array}
\right.
$
is equivalent to
$$
\left\{
\begin{array}{ccc}
a^2 &=&\frac{1}{2}\left( \sqrt{x^2+y^2} + x\right), \\
b^2 &=&\frac{1}{2}\left( \sqrt{x^2+y^2} -x\right).
\end{array}
\right.
$$
Therefore $$z^2 = Z \Rightarrow
\left\{
\begin{array}{ccc}
a^2 &=&\frac{1}{2}\left( \sqrt{x^2+y^2} + x\right), \\
b^2 &=&\frac{1}{2}\left( \sqrt{x^2+y^2} -x\right), \\
\mathrm{sgn}(ab) &= & \mathrm{sgn}(y).
\end{array}
\right.
$$
The converse is true, since these last equations imply
$$4a^2 b^2 = \left( \sqrt{x^2+y^2} + x\right) \left( \sqrt{x^2+y^2} -x\right) = x^2+y^2-x^2 = y^2,$$
and since $\mathrm{sgn}(ab) = \mathrm{sgn}(y)$, we conclude $2ab=y$. So we have proved the equivalence
$$z^2 = Z \iff
\left\{
\begin{array}{ccc}
a^2 &=&\frac{1}{2}\left( \sqrt{x^2+y^2} + x\right), \\
b^2 &=&\frac{1}{2}\left( \sqrt{x^2+y^2} -x\right), \\
\mathrm{sgn}(ab) &= & \mathrm{sgn}(y).
\end{array}
\right.
$$
As $x^2+y^2 \geq x^2, \sqrt{x^2+y^2} \geq \vert x \vert $, and $\vert x \vert \geq x, \vert x \vert \geq -x$, so
\begin{align*}z^2 = Z &\iff
\left\{
\begin{array}{ccl}
a &=&\varepsilon \sqrt{\frac{1}{2}\left ( \sqrt{x^2+y^2} + x\right)} \\
b &=&\varepsilon\ \mathrm{sgn}(y)\sqrt{\frac{1}{2}\left( \sqrt{x^2+y^2} -x\right)},\qquad \varepsilon \in \{-1,1\} \\
\end{array}
\right.\\
&\iff z \in \{ z_0, - z_0 \},
\end{align*}
where $$z_0 = \sqrt{\frac{1}{2}\left ( \sqrt{x^2+y^2} + x\right)} + i \ \mathrm{sgn}(y)\sqrt{\frac{1}{2}\left( \sqrt{x^2+y^2} -x\right)}.$$
Conclusion: Every $z \in \mathbb{C}$ has a square root in $\C$.
\end{enumerate}
\end{proof}
\paragraph{Ex. 3.2.3}
{\it Use the IVT to prove that every positive real number $a$ has a real square root.
}
\begin{proof}
Suppose that $a \in \mathbb{R}^+$.
Let $u:\mathbb{R} \to \mathbb{R}$ defined by $x\mapsto u(x) = x^2 -a$.
Then $u$ is continuous, $u$ is strictly increasing, and
$u(0) = -a \leq 0, \lim\limits_{x\to \infty} u(x) = + \infty$ (so there exists $A \in \R^{+}$ such that $u(A)>0$).
By the Intermediate Value Theorem, there exists a unique $b\in \mathbb{R}^+$ such that $b^2 = a$, so $a$ has a real square root.
\end{proof}
\paragraph{Ex. 3.2.4}
{\it A field $F$ is an ordered field if there is a subset $P \subset F$ such that:
\begin{enumerate}
\item[(a)] $P$ is closed under addition and multiplication.
\item[(b)] For any $a\in F$, exactly one of the following is true: $a \in P, a = 0$, or $-a\in P$.
\end{enumerate}
One then defines $a>b$ to mean $a-b\in P$ (so that $P$ becomes the set of positive elements). From this, one can prove all the typical properties of $>$. Now let $F$ be an ordered field. Prove that $-1$ is not a square in $F$.
}
\begin{proof}
Let $F$ an ordered field.
Since $P$ is closed under multiplication by (a), if $a \in P$, then $a^2 \in P$.
If $-a \in P$, $a^2 = (-a)(-a) \in P$. By (b), every $a\in F$ verifies $a\in P$, or $a=0$, or $-a\in P$, so we can conclude that
\begin{align}
\forall a,\ a \in F^* \Rightarrow \ a^2 \in P. \label{eq3.2.4:1}
\end{align}
So $P$ contains all squares in $F$, $0$ excluded.
By definition of fields, we know that $1\neq 0$, so $1 = 1^2 \in P$.
By (b), the three cases $a\in P$, $a=0$, $-a\in P$ are mutually exclusive, thus $-1 \not \in P$.
Therefore $-1$ is not a square in $F$, otherwise $-1 = a^2 \in P$ by \eqref{eq3.2.4:1}.
Conclusion: $-1$ is not a square in the ordered field $F$.
\end{proof}
\paragraph{Ex. 3.2.5}
{\it Let $F$ be a real closed field. As in the text, this means that $F$ is an ordered field (see Exercise 4) such that every positive element of $F$ has a square root in $F$ and every $f\in F[x]$ of odd degree has a root in $F$.
\begin{enumerate}
\item[(a)] Use Exercise 4 to show that $x^2 + 1$ is irreducible over $F$. Then define $F(i)$ to be the field $F[x]/\langle x^2+1\rangle$. By the Cauchy construction described in Section 3.1, elements of $F(i)$ can be written $a+bi$ for $a,b\in F$.
\item[(b)] Show that every quadratic polynomial in $F(i)$ splits completely over $F(i)$.
\item[(c)] Prove that $F(i)$ is algebraically closed.
\end{enumerate}
}
\begin{proof}
\begin{enumerate}
\item[(a)]
Since $-1$ is not a square in $F$ by Exercise 4, the polynomial $x^2+1$ has no root in $F$, and it has degree 2, thus it is irreducible over $F$.
Therefore $F(i) = F[x]/\langle x^2+1\rangle$ is a field, where $i = x + \langle x^2 + 1 \rangle$, by Proposition 3.1.1.
The division of any polynomial $f$ by $x^2+1$ gives $$f= q (x^2+1) + bx+a,$$ so every $y \in F(i)$ is of the form $y = a+ ib$.
\item[(b)] Let $ax^2+bx+c,\ a,b,c \in F(i), a\neq 0$, any quadratic polynomial.
\begin{align*}
a x^2+bx+c &= a\left(x^2+ \frac{b}{a}x + \frac{c}{a}\right)\\
&=a\left[\left(x+\frac{b}{2a}\right)^2 -\frac{b^2}{4a^2} + \frac{c}{a}\right]\\
&=a\left[\left(x+\frac{b}{2a}\right)^2 -\frac{\Delta}{4a^2}\right] , \Delta = b^2-4ac\\
\end{align*}
By definition of a real closed field, every positive element of $F$ has a square root in $F$. With the same proof as in Ex 3.2.2, we can prove that every $z \in F(i)$ has a square root. One square root of $z = x + iy,\ x,y \in F,$ is given by
$$z_0 = \sqrt{\frac{1}{2}\left ( \sqrt{x^2+y^2} + x\right)} + i \ \mathrm{sgn}(y)\sqrt{\frac{1}{2}\left( \sqrt{x^2+y^2} -x\right)}.$$
We will write $\sqrt{\Delta}$ one of the square roots of $\Delta$. Then
\begin{align*}
ax^2+bx+c &= a\left[\left(x+\frac{b}{2a}\right)^2 -\left (\frac{\sqrt{\Delta}}{2a}\right)^2\right]\\
&=a(x-x_1)(x-x_2), x_1 = \frac{-b-\sqrt{\Delta}}{2} \in F(i), x_2 = \frac{-b+\sqrt{\Delta}}{2} \in F(i)
\end{align*}
splits completely over $F(i)$.
\item[(c)]
By definition of a real closed field, and by (b),
$\bullet$ every polynomial of odd degree in $F[x]$ has a root in $F$,
$\bullet$ every element $a \in F(i)$ has a square root in $F(i)$,
$\bullet$ every quadratic polynomial $f \in F(i)[x] $ splits completely over $F(i)$.
The Proposition 3.2.2 and the Lemme 3.2.3 are so satisfied if we replace $\R$ by $F$ and $\C$ by $F(i)$.
Theorem 3.2.4 for $F(i)$ follows, with the same proof: $F(i)$ is an algebraically closed field.
\end{enumerate}
\end{proof}
\paragraph{Ex. 3.2.6}
{\it Here is yet another way to state the Fundamental Theorem of Algebra.
\begin{enumerate}
\item[(a)] Suppose that $f(\alpha) = 0$, where $f\in \R[x]$ and $\alpha \in \C$. Prove that $f(\overline{\alpha}) = 0$.
\item[(b)] Prove that the Fundamental Theorem of Algebra is equivalent to the assertion that every nonconstant polynomial in $\R[x]$ is a product of linear and quadratic factors with real coefficients.
\end{enumerate}
}
\begin{proof}
\begin{enumerate}
\item[(a)] Let $f \in \mathbb{R}[x]$, and suppose that $f(\alpha)=0$. Then $\overline{f} = f$, and $\overline{f}(\alpha)=0$.
By Ex. 3.3.1(b), this implies $f(\overline{\alpha}) =0$.
Conclusion : if $f \in \mathbb{R}[x]$, $$f(\alpha)=0 \Rightarrow f(\overline{\alpha})=0.$$
\item[(b)]
$\bullet$ Suppose that every nonconstant polynomial in $\mathbb{C}[x]$ has a root in $\mathbb{C}$.
Name $x_1,\cdots, x_r$ the real roots of $f$ : $f = a(x-x_1)^{k_1}\cdots(x-x_r)^{k_r}g$, where $a \in \mathbb{R}$, and $g \in \mathbb{R}[x]$ is monic and has no real root.
We show by induction on $d$ that every polynomial $g \in \mathbb{R}[x]$ without real root, monic, of degree $d$, is product of monic quadratic real polynomials.
If $d=0$, $g=1$ is the empty product.
We suppose $d>0$, and put the induction hypothesis that every polynomial in $ \mathbb{R}[x]$ without real root, monic, of degree less than $d$, is product of monic quadratic real polynomials.
Let $g \in \R[x]$ a polynomial of degree $d$ without real root. $g$ has by hypothesis a complex root $\alpha$. Then $g = (x-\alpha)g_1, g_1\in \mathbb{C}[X]$.
By (a), $\overline{\alpha}$ is a root of $g$. $0 = g(\overline{\alpha}) = (\overline{\alpha} - \alpha) g_1(\overline{\alpha})$, and $\overline{\alpha} \neq \alpha$, thus $g_1(\overline{\alpha})=0$, $g_1 = (x- \overline{\alpha}) h, h \in \mathbb{C}[x]$, therefore
$$g = (x-\alpha)(x-\overline{\alpha}) h, \ h \in \mathbb{C}[x].$$
$u = (x-\alpha)(x-\overline{\alpha}) = x^2 +sx+t$, where $s = \alpha+ \overline{\alpha} \in \mathbb{R}, t=\alpha\overline{\alpha} \in \mathbb{R}$, thus $u \in \mathbb{R}[x]$, and also $h\in \mathbb{R}[x]$, since $h$ is the quotient of the Euclidean division of $g$ by $u$.
$g = (x^2 - s x + t) h$, where $h \in \mathbb{R}[x]$ is monic, of degree less than $d$, without real root. By the induction hypothesis, $h$ is product of monic real quadratic polynomials, thus it is the same for $g$, and the induction is done.
Consequently, $f$ is product of linear or quadratic factors with real coefficients.
$\bullet$ Conversely, suppose that every polynomial in $\R[x]$ is product of linear or quadratic factors with real coefficients.
Let $f \in \C[x]$, with $\deg(f) \geq 1$. We will show that $f$ has a complex root.
By hypothesis $f$ has a linear or a quadratic factor.
If $f$ has a linear factor $ax+b$, then $-b/a$ is a (real) root of $f$, and if $f$ has a factor $ax^2+bx+c, \ a \ne 0$, then Lemma 3.2.3 and Exercise 3.2.2 show that $f$ has a complex root. In both cases, $f$ has a complex root, so every non constant polynomial in $\C[x]$ has a complex root.
\end{enumerate}
\end{proof}
\paragraph{Ex. 3.2.7}
{\it Prove that a field $F$ is algebraically closed if and only if every nonconstant polynomial in $F[x]$ has a root in $F$.
}
\begin{proof}
By definition, a field $F$ is algebraically closed if every nonconstant polynomial is product of linear factors in $F[x]$.
$\bullet$ If $F$ is algebraically closed, and if $f\in F[x]$ is not a constant, this product of linear factors is not empty, so $f$ is divisible by a linear factor $ax+b, a,b \in F$. Hence $f$ has a root $\alpha = -b/a$ in $F$.
$\bullet$ Suppose that every nonconstant polynomial has a root in $F$
We show by induction on $d$ that every polynomial $f \in F[x], d = \deg(f) >0$, is product of linear factors in $F[x]$
If $d=1$, $f = ax+b, \ a\ne 0$, is product of one linear factor.
Let $f \in F[x], d = \deg(f) >1$. Then $f$ has by hypothesis a root $\alpha \in F$, so $f = (x-a)g$, where $\deg(g)<d$. By the induction hypothesis, $g$ is a constant or is product of linear factors, so it is the same for $f$, and the induction is done.
Conclusion: If $F$ is an algebraically closed field, then the two following propositions are equivalent:
\begin{enumerate}
\item[(i)] Every nonconstant polynomial in $F[x]$ is product of linear factors.
\item[(ii)] Every nonconstant polynomial in $F[x]$ has a root in $F$.
\end{enumerate}
\end{proof}
\end{document}